2012
DOI: 10.1371/journal.pone.0041393
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Deletion of the Streptococcus pneumoniae Lipoprotein Diacylglyceryl Transferase Gene lgt on ABC Transporter Function and on Growth In Vivo

Abstract: Lipoproteins are an important class of surface associated proteins that have diverse roles and frequently are involved in the virulence of bacterial pathogens. As prolipoproteins are attached to the cell membrane by a single enzyme, prolipoprotein diacylglyceryl transferase (Lgt), deletion of the corresponding gene potentially allows the characterisation of the overall importance of lipoproteins for specific bacterial functions. We have used a Δ lgt mutant strain of Streptoco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
62
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(79 citation statements)
references
References 82 publications
(137 reference statements)
13
62
1
Order By: Relevance
“…For several Gram-positive bacteria, others demonstrated that, in the absence of functional Lgt, prolipoproteins were in decreased abundance in the cell membrane but in greater abundance in culture supernatants (11,21). This was also confirmed for a S. pneumoniae lgt deletion mutant (10). We constructed an lgt deletion mutant in our vaccine background strain, strain RM200, by insertional deletion of a spectinomycin resistance cassette in place of lgt.…”
Section: Wcv-induced T H 17 Responses and Protection Against Np Colonsupporting
confidence: 65%
See 3 more Smart Citations
“…For several Gram-positive bacteria, others demonstrated that, in the absence of functional Lgt, prolipoproteins were in decreased abundance in the cell membrane but in greater abundance in culture supernatants (11,21). This was also confirmed for a S. pneumoniae lgt deletion mutant (10). We constructed an lgt deletion mutant in our vaccine background strain, strain RM200, by insertional deletion of a spectinomycin resistance cassette in place of lgt.…”
Section: Wcv-induced T H 17 Responses and Protection Against Np Colonsupporting
confidence: 65%
“…To address this question, we generated an lgt deletion mutant in our colonization strain, clinical serotype 6B pneumococcus 0603. Deletion of lgt in other pneumococcal strains has been shown to attenuate the ability of the bacteria to colonize, as evidenced by earlier clearance of ⌬lgt pneumococci from nasal washes from mice following intranasal infection (10). To evaluate whether our mutant 0603 strain could successfully colonize mice, we intranasally challenged naive C57BL/6 mice with the live ⌬lgt 0603 mutant strain.…”
Section: Wcv-induced T H 17 Responses and Protection Against Np Colonmentioning
confidence: 99%
See 2 more Smart Citations
“…S. aureus and its mutants lacking lipoteichoic acid (⌬ltaS) or D-alanylation of teichoic acids (⌬dltA) stimulated NO production in a murine macrophage cell line; however, the ⌬lgt mutant failed to induce NO production in a dose-dependent manner (36). These results suggest that not lipoteichoic acid (LTA) but Lpp of S. aureus induce NO production in murine Like many other bacteria, S. pneumoniae ⌬lgt mutants hardly can grow in blood, bronchoalveolar lavage fluid, or cation-depleted medium, and virulence is attenuated in mouse models such as nasopharyngeal colonization, where sepsis or pneumonia was significantly decreased (38). Furthermore, in ⌬lgt mutants, TLR2 signaling is significantly decreased, and it appears that the leukocyte responses to Lpp are required for TLR2-and IL-1R-associated kinase-4-mediated inflammatory responses to S. pneumoniae (39).…”
Section: Maturation Of Pre-lpp Is Crucial For Pathogenicity and Inflamentioning
confidence: 96%